The Role of the Ministry of Human Rights in Combating Radicalism againts Students - Nita, Age Tiara; Kartika, Sherina Dwi; Ambarini, Nur Sulistyo Budi (Jurnal Idea Hukum, 2025)
Radicalism poses a serious threat to state integrity and democracy. In Indonesia, it has increasingly affected the younger generation, including students. A human rights approach is crucial in fostering public understanding of tolerance and Pancasila as the foundation of state ideology. To counter radicalization effectively, collaboration between the government, educational institutions, and society is essential. One key institution in this effort is the Ministry of Human Rights, which plays a role in promoting legal awareness and human rights education. This study aims to examine its role in countering radicalism among students. Using a normative legal research method through literature and legal document analysis, this study explores how government policies address radicalization in educational environments. Findings indicate that preventing violence, intolerance, and terrorism requires a comprehensive strategy that integrates legal, educational, and social approaches. While a human rights perspective is vital, it must be supported by concrete actions, including legal education programs, student engagement initiatives, and policy reforms. The government must ensure that human rights protection is not merely conceptual but has real impacts on students and society. The Ministry of Human Rights can strengthen its role by developing collaborative programs with universities and civil society, integrating human rights education into curricula, and ensuring policies that safeguard students from radical influences. Through these efforts, radicalism can be countered effectively while upholding democratic values and national unity. Keywords: Basic; Rights; Radicalism; Students.